(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT The significance of the Holy Qur’an is its illumination of a divine tradition that afflicts many modern human societies. These societies benefit from divine grace and interpret their fate in the same way as previous villages and nations that disbelieved and were overwhelmed by God’s blessings upon them. The Qur’an provides a methodology for responding to this fate. As an omnipotent and righteous entity, God Almighty’s ultimate destiny was destruction and extinction. The research will be structured into an introduction, preface, and two topics. Regarding the second topic, it pertains to the destruction of crops and fruits belonging to the beneficiaries.